Dividendes En Présence Des Imperfections Du Marché - Riad Lamyaa; Touili Karima (European Scientific Journal, ESJ, 2017)
The topic of the company's dividend policy has captured the interest of economists and over the last five decades has been the subject of several theoretical and empirical studies. Economists have proposed a number of theories to explain the dividend puzzle. The purpose of this paper is to examine the effect of market imperfections (asymmetric information, agency costs and the impact of taxation) on corporate dividend policy. While briefly presenting the main theories of dividend policy and summarizing the empirical evidence on these theories. The paper reaches at a conclusion that the famous dividend puzzle is still unresolved. The empirical evidence is ambiguous and the search for a new explanation of dividends is continuing.